Optimizing the Development of Ecotourism Potential of Lemor Botanical Garden as a Tourist Attraction - Dita Yupani; Jasmine Chanifah Uzdah Bachtiar; Getachew Melesse Asefa; Bishow Poudel (Tinta Emas Publisher, 2024)
Indonesia natural diversity supports a thriving tourism industry, including in Lombok Timur Regency, which is known for its natural attractions. Among these is the Lemor Botanical Garden, a conservation and tourism site covering 82.9 hectares with 282 plant species. Despite offering various facilities, the absence of adequate informational graphics hinders visitors from locating essential amenities such as toilets, prayer rooms, and specific areas, reducing their overall comfort and satisfaction. This descriptive qualitative study was conducted at Lemor Botanical Garden, Lombok Timur. Primary data were obtained through observation and interviews, while secondary data were collected from books and journals. The analysis used Milles and Huberman's interactive model, with triangulation and member checking ensuring the validity of findings. The research also examined the garden’s potential as a natural laboratory for geography education, using three main indicators. The findings highlight the need for improving signage and transportation facilities to enhance accessibility and visitor experience. Active participation of POKDARWIS in management is crucial, particularly in providing tour guides and security personnel. Further recommendations include the introduction of environmental education, conservation programs, and cultural activities. Improved visitor facilities, such as prayer rooms, toilets, dining areas, and better accessibility, are also essential to support sustainable tourism. Lemor Botanical Garden holds substantial potential for ecotourism development due to its rich biodiversity and scenic beauty. However, challenges such as limited promotion and competition from other destinations must be addressed. Strengthening infrastructure, enhancing visitor engagement, and prioritizing conservation can ensure its long-term sustainability while benefiting the local community.